UPAYA MENINGKATKAN PEMBELAJARAN SEPAKBOLA DENGAN MEDIA GAWANG SIMPAI (Department of Physical Education, Sport, Health and Recreation, 2014)
The problem from this research if holahoop can increase football learning for 5th grade SD kaligangsa 4 Tegaleducation year 2012/2013 while the aim from this research is to know how far holahoop media can increasefootball learning in 5th grade of SD Kaligangsa 4 Tegal education year 2012/2013. The research instrumen uselearning implementation observation paper, student’s motivation of study observation paper, student responsequestionnaire and practice test. The technique of data analysis is using descriptively and by counting a formulawhich has determined. The successfull of this research can said if the students get the completeness and theresult of student’s learning from cycle I to cycle II. The result which is get from learning football game is incognitive aspect, affective, and psychomotor with KKM 75 in first cycle only get average score 75,27 or around57,70% complete and still in category deficient, while in second cycle learning the result is getting better scorethat is 83,81 and be avowed all students has been completed.